(untitled) (Fiep Bulletin - online, 2013)
The project Open school began in Novo Hamburgo in 2005, in a partnership between Federal government and UNESCO, near with city hall. The project is to open schools on weekends, offering sports, cultural, vocational and leisure activities. These activities look to serve all members of the local community. Sports are the activities most looking by comunity. Given the open school project objective of creating communities in a culture of peace, we know of people working in the community and at school (parents and project coordinators in schools) if the project can arrive the objective. This study is characterized as a qualitative descriptive and exploratory search. Developers were the coordinators and parents of participants in the Open School Program in nine schools of the district Straws in the city of Novo Hamburgo/RS. Were used as research tools to semi-structured interviews, observations and fieldwork. The analysis was divided into three categories: Interlude violence: rule limit and sense of belonging; Leisure space and community school opened: the involvement of parents. The analysis used the technique of triangulation of sources. After the analyzing of dates, is evident that the Open School project is an important community space, as has been consolidated as a locus for the year of peace that cannot reach the structures of the violence processes of the district over the years, through its actions, fostering a sense of belonging to a community among participants.